Morphological characteristics and chemical composition of placer gold from the Kengevey River basin and first data on associated platinum-metal mineralization (Magadan region) - E.D. Skilskaia; Sh.S. Kudaeva (Вестник Камчатской региональной ассоциации "Учебно-научный центр". Серия: Науки о Земле, 2023)
The paper presents the results of the study of typomorphic characteristics of placer gold of the tributaries of the Kengeveem River, Magadan region. Placer gold was studied by optical and scanning electron microscopy at the Institute of Volcanology and Seismology of the Far East Branch of the Russian Academy of Sciences. As a result, the first information on the morphology, internal structure and chemical composition of placer gold from the southeastern part of the Taigonos Peninsula was obtained. Three types of the gold were determined. The first type is dominant. The grains are chacterized by sub-ore morphology, with weak and medium degrees of roundness. Only Au-Ag is present in the composition of native gold, other macrocomponents were not found. The gold grade is 750–950 ‰. Some gold grains bear signs of hypergene transformation, expressed in the development of high-grade gold rims and intergrain veins. The second type of gold is represented by well-rounded lamellar extractions with a grade of 980–990 ‰. The third type is loose aggregates of secondary high-grade mustard gold. The obtained data allowed us to determine the different drift distances of native gold and to consider the low-sulfide epithermal Au-Ag mineralization and presumably far-distant gabbroids as the primary sources of gold.